PAEDIATRIC TRAUMATIC CARDIAC ARREST: DATA FROM THE JOINT THEATRE TRAUMA REGISTRY. Issue 9 (14th August 2014) - Hillman, Christopher M; Rickard, Annette; Rawlins, Matthew; Smith, Jason
Abstract : Objectives & Background: Traumatic cardiac arrest (TCA) in children is associated with poor survival (<5% in the majority of studies) and even worse neurological outcome. Since 2003, over 600 seriously injured local national children have been treated at deployed UK military medical treatment facilities during the Iraq and Afghanistan conflicts. A number of these were in cardiac arrest after sustaining traumatic injuries . Trauma care has continually advanced during the recent conflicts, leading to many unexpected survivors (1). The objective of this study was to define outcomes from paediatric TCA in this cohort. Methods: A retrospective database review was undertaken using the Joint Theatre Trauma Registry. This includes UK military, coalition military, civilians, and local security forces personnel who prompted trauma team activation. However, all children in this series were local nationals. All children aged less than 18 years who presented between January 2003 and April 2014, and who underwent CPR, were included. Results: 32 children with TCA were included. The mechanisms of injury were IED (improvised explosive device), GSW (gunshot wound), MVC (motor vehicle collision), drowning and others (rocket propelled grenade, unexploded ordnance) – see Table 1. 4 children survived to discharge from the medical treatment facility (12.5%), though no data are available regarding the long-term neurological outcome in these patients. Further analyses, in particular with regard to injury patterns and life saving interventions, are underway. Conclusion: Outcomes from this cohort show better survival rates in paediatric traumatic cardiac arrest compared to the most other studies. The reason for this is not known, although this mirrors the unexpected survivors previously reported in recent military series. Further work is necessary to define the optimal management of paediatric patients in TCA.